Author cocitation analysis : quantitative methods for mapping the intellectual structure of an academic discipline - Eom, Sean B. (Hershey, PA : Information Science Reference, 2009)
'This book introduces an alternative approach to conducting author cocitation analysis (ACA) without relying on commercial citation databases such as index ISI citation index. It is based on a custom bibliographic database and cocitation matrix generation systems specifically developed to use the custom database'--Provided by publisher
'Premier reference source'--Cover
Includes bibliographical references and index
Keywords: Bibliometrics; Bibliography -- Databases; Multivariate analysis; Research -- Statistical methods -- Data processing